Mekanisme Lalu Lintas Pembayaran Luar Negeri dalam Kegiatan Ekspor - Dea Dellia; Dwi Ananda; Lilis Apriyaningsih; Windi Aulia; Dwita Sakuntala (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to discuss the foreign payment traffic mechanism in export and import activities, which is an important aspect of international trade. In the current context of globalization, trade transactions cannot be carried out only by relying on direct relations between exporters and importers. It requires oversight from multilateral institutions, such as the World Trade Organization (WTO), to ensure smoothness and fairness in such transactions. An effective payment mechanism is essential to ensure that payments are made on time and in accordance with the agreement, thus increasing trust between the parties involved. This research uses a qualitative approach with data collection through literature study, document analysis, and interviews with experts in the field of international trade and banking.